Actions to improve safety and health in construction (Luxembourg, 2004)
"Construction industries, with an annual turnover in excess of EUR 900 billion and nearly 13 million employees in the EU-15 Member States alone. Unfortunately, it is also one of the most dangerous. More construction workers are killed, injured or suffer ill-health than in any other industry."